Examining Moral Typologies in Decision-Making Regarding Socio-Scientific Issues: Students' Interpretations of Right and Wrong: Penelitian - Nadia Mubarokah; Ince Raudhiah Zahra; Suci Indah Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aimed to examine the typology of students’ moral judgment in decision-making related to socio-scientific issues. A Systematic Literature Review (SLR) method was employed to analyze 22 national and international journal articles addressing four moral typologies: absolutists, subjectivists, situationists, and exceptionists, as well as the decision-making processes within the context of socio-scientific issues. The research stages included formulating research questions, searching and selecting relevant literature, and conducting an in-depth analysis to identify decision-making tendencies based on moral typology. Findings revealed that absolutist students uphold universal moral values with an emphasis on social and environmental concerns; subjectivist students base their decisions on personal values influenced by religion and culture; situationist students adjust their decisions according to the specific situational context without consistently adhering to general moral standards; and exceptionist students choose decisions perceived to yield the greatest positive impact despite being aware of moral norms. Understanding moral typology helps educators design.